Experimental models of antibiotic exposure and atopic disease - Donald, Katherine; Finlay, B. Brett (Frontiers in Allergy, 2024)
In addition to numerous clinical studies, research using experimental models have contributed extensive evidence to the link between antibiotic exposure and atopic disease. A number of mouse models of allergy have been developed and used to uncover the specific effects of various microbiota members and perturbations on allergy development. Studies in mice that lack microbes entirely have also demonstrated the various components of the immune system that require microbial exposure. The importance of the early-life period and the mechanisms by which atopy “protective” species identified in human cohorts promote immune development have been elucidated in mice. Finally, non-animal models involving human-derived cells shed light on specific effects of bacteria on human epithelial and immune responses. When considered alongside clinical cohort studies, experimental model systems have provided crucial evidence for the link between the neonatal gut microbiota and allergic disease, immensely supporting the stewardship of antibiotic administration in infants. The following review aims to describe the range of experimental models used for studying factors that affect the relationship between the gut microbiota and allergic disease and summarize key findings that have come from research in animal and in vitro models.